Impact of UPLC-MS in Food and Drug/Metabolite Analysis - Semwal, Ankit; Dogra, Raghav; Verma, Kritika; Bhatia, Rohit (Current Pharmaceutical Analysis, 2021)
The hyphenation of Ultra-Performance Liquid performance (UPLC) with mass spectrometry (MS) has emerged as a powerful tool in analytical research due to its advanced sensitivity, resolution and speed. Its advanced instrumentation, specialized columns, separation at ultra-high pressure and sophisticated software are the distinguishing features as compared to the traditional separating techniques. It has a wide range of applications in various fields such as analysis of food stuffs, drug metabolites, beverages, toxicology, soil samples and micronutrient analysis. In the present compilation, authors have highlighted the applicability of UPLC-MS in the analysis of food stuffs and drug metabolites along with the various optimized analytical conditions and obtained results.
Keywords: HPLC